The impact of extent of resection in surgical outcome of pilomyxoid astrocytoma: a case study - Chaulagain, Dipak; Smolanka, Volodymyr I.; Smolanka, Andriy V.; Havryliv, Taras S. (Ukrainian Neurosurgical Journal, 2021)
The pilomyxoid astrocytoma (PMA) is a rare glioma that has recently been identified as a separate entity and is frequently found in the hypothalamic region. PMA is a subtype of pilocytic astrocytoma (PA), with clinical, histological, and molecular data indicating a close relationship as well as more aggressive biological behaviour in the former. There is still doubt in surgical outcome of PMA that the extent of resection, independent of location or age, is a key factor of recurrence and subsequent therapeutic choices. However, further study is needed to better understand its behaviour and, as a result, establish a consensus on its management. This research features a 2-year-6-month-old female who sought medical attention after complaining of weight loss for four weeks and vomiting for two weeks prior to her visit to the doctor. She had no additional symptoms. Only bilateral pailledema was found during the physical examination. The magnetic resonance imaging (MRI) scans revealed a tumor in the sellar area with heterogeneous enhancement. The patient had ventriculoperitoneal (VP) shunting followed by partial tumor excision twice (Extent of resection 35 percent followed by 16 percent as total 51 percent). The histology and immunohistochemical investigations revealed typical PMA characteristics. Adjuvant treatment, which included chemotherapy and radiosurgery, was initiated for the patient. She has been asymptomatic for two years and has showed no indications of progression of the disease on follow-up scans.